Babesiosis and anaplasmosis in dairy cattle in Northeastern Brazil - Souza,Francisco de A.L. (2013)
The goal of this study was to characterize the epidemiological situation and the factors involved in the prevalence of babesiosis and anaplasmosis in cattle in the dairy basin of Parnaíba, Piauí, Brazil. The study was conducted in 22 farms, and collected blood samples from 202 cattle to study serological, molecular and determination of the packed cell volume (PCV). On the farms were applied surveys involving epidemiological aspects. Seroprevalence rates were: Babesia bigemina 52.5%, B. bovis 68.8%, and Anaplasma marginale 89.1%. Of the samples analyzed, 73.3% were reactive for Babesia spp. and A. marginale, showing co-infection. In PCR, B. bigemina and B. bovis were positive in 52.0% and 33.2% respectively, and A. marginale in 76.2%. Of these, 51.5% amplified DNA of Babesia spp. and A. marginale. The semi-intensive management predominated in 68.0% of the farms studied. The clinical history of babesiosis and anaplasmosis, was reported from 73% of the farms. There was no significant difference (p>0.05) between age groups and for the PCV of positive compared with negative animals. The study indicates that in this region is enzootic instability for babesiosis and enzootic stability for anaplasmosis, reinforcing the fact that in Brazil there are areas of enzootic instability, even in tropical regions of the country. The PCR technique was a valuable tool for the diagnosis of these diseases and may be used to characterize a geographic region.